2009
DOI: 10.1253/circj.cj-08-1209
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Ischemia

Abstract: Although much progress has been made in reducing mortality from ischemic cardiovascular disease, this condition remains the leading cause of death throughout the world. This might in part be due to the fact that over half of patients have a catastrophic event (heart attack or sudden death) as their initial manifestation of coronary disease. Contributing to this statistic is the observation that the majority of myocardial ischemic episodes are silent, indicating an inability or failure to sense ischemic damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 114 publications
1
61
0
4
Order By: Relevance
“…Several factors have been related to the absence of symptoms during myocardial ischemia, but the precise mechanisms responsible for the lack of pain have not yet been fully elucidated [1,7,8,9]. Several studies have shown that in patients with SMI, the threshold of pain perception and tolerance are significantly higher than in symptomatic patients [8,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors have been related to the absence of symptoms during myocardial ischemia, but the precise mechanisms responsible for the lack of pain have not yet been fully elucidated [1,7,8,9]. Several studies have shown that in patients with SMI, the threshold of pain perception and tolerance are significantly higher than in symptomatic patients [8,27].…”
Section: Discussionmentioning
confidence: 99%
“…Silent myocardial ischemia (SMI) is defined as an objective documentation of myocardial ischemia in the absence of angina or anginal equivalents [1]. …”
Section: Introductionmentioning
confidence: 99%
“…By definition, any symptoms of cardiac ischemia must be absent in order to make the diagnosis of silent ischemia [6]. However, elderly people without a history of cerebral infarction often present with atypical symptoms of myocardial infarction, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cerebral responses have been shown to be different between patients with angina and those with silent myocardial ischemia during systemic dobutamine infusion (Rosen et al 1996), although silent myocardial ischemia may be associated with both functional and organic abnormalities (Canto et al 2000;Gutterman 2009). Therefore, CEPs in response to selective electrical stimulation of the heart could be useful for examining the pathophysiology of cardiac anxiety and/or silent myocardial ischemia.…”
Section: Possible Application Of Ceps In Response To Cardiac Electricmentioning
confidence: 99%
“…In general, females and patients with psychiatric disorders are more prone to palpitation and/or chest pain without organic heart disease (cardiac anxiety) (Serlie et al 1995;Barsky et al 1996;Ehlers et al 2000;Barsky 2001). In contrast, arrhythmias are often asymptomatic (Barsky 2001), and painless cardiac ischemic events (silent myocardial ischemia), which are associated with poor prognosis (Canto et al 2000;Gutterman 2009), are common. Therefore, it is clinically important to elucidate the mechanisms of cardiac sensation in order to improve the quality of life of patients with complaining of cardiac sensation, as well as to improve the prognosis of cardiovascular disease.…”
mentioning
confidence: 99%